Blended care in the treatment of subthreshold symptoms of depression and psychosis in emerging adults: A randomised controlled trial of Acceptance and Commitment Therapy in Daily-Life (ACT-DL). (May 2020) - van Aubel, Evelyne; Bakker, Jindra Myrthe; Batink, Tim; Michielse, Stijn; Goossens, Liesbet; Lange, Iris; Schruers, Koen; Lieverse, Ritsaert; Marcelis, Machteld; van Amelsvoort, Thérèse; van Os, Jim; Wichers, Marieke; et al.
Abstract: In this study, the feasibility and efficacy of Acceptance and Commitment Therapy in Daily Life (ACT-DL), ACT augmented with a daily life application, was investigated in 55 emerging adults (age 16 to 25) with subthreshold depressive and/or psychotic complaints. Participants were randomized to ACT-DL (n = 27) or to active control (n = 28), with assessments completed at pre- and post-measurement and 6- and 12-months follow-up. It took up to five (ACT-DL) and 11 (control) months to start group-based interventions. Participants attended on average 4.32 out of 5 ACT-DL sessions. On the app, they filled in on average 69 (48%) of signal-contingent beep-questionnaires, agreed to 15 (41%) of offered beep-exercises, initiated 19 on-demand exercises, and rated ACT-DL metaphors moderately useful. Relative to active control, interviewer-rated depression scores decreased significantly in ACT-DL participants (p = .027). Decreases in self-reported depression, psychotic-related distress, anxiety, and general psychopathology did not differ between conditions. ACT-DL participants reported increased mean NA (p = .011), relative to active controls. Mean PA did not change in either group, nor did psychological flexibility. ACT-DL is a feasible intervention, although adaptations in future research may improve delivery of and compliance with the intervention. There were mixed findings for its efficacy in reducing subthreshold psychopathology in emerging adults. Dutch Trial Register no.: NTR3808. Highlights: EMI-augmented ACT is a feasible intervention in non-help-seeking emerging adults. Objective depressive symptoms reduce more in ACT-DL than in active control. Self-reported psychopathology reduces equally in ACT-DL compared to active control. Daily-life NA was increased in ACT-DL, compared to a decrease in active control. ACT-DL did not have an effect on psychological flexibility, nor on daily life PA.